The Effects of Menopause Hormone Therapy on Lipid Profile in Postmenopausal Women: A Systematic Review and Meta-Analysis - Nie, Guangning; Yang, Xiaofei; Wang, Yangyang; Liang, Wanshi; Li, Xuewen; Luo, Qiyuan; Yang, Hongyan; Liu, Jian; Wang, Jiajing; Guo, Qinghua; Yu, Qi; Liang, Xuefang (Frontiers in Pharmacology, 2022)
Importance: The incidence of dyslipidemia increases after menopause. Menopause hormone therapy (MHT) is recommended for menopause related disease. However, it is benefit for lipid profiles is inconclusive. Objective: To conduct a systematic review and meta-analysis of randomized controlled trials to evaluate the effects of MHT on lipid profile in postmenopausal women. Evidence Review: Related articles were searched on PubMed/Medline, EMBASE, Web of Science, and Cochrane Library databases from inception to December 2020. Data extraction and quality evaluation were performed independently by two reviewers. The methodological quality was assessed using the “Cochrane Risk of Bias checklist”. Results: Seventy-three eligible studies were selected. The results showed that MHT significantly decreased the levels of TC (WMD: −0.43, 95% CI: −0.53 to −0.33), LDL-C (WMD: −0.47, 95% CI: −0.55 to −0.40) and LP (a) (WMD: −49.46, 95% CI: −64.27 to −34.64) compared with placebo or no treatment. Oral MHT led to a significantly higher TG compared with transdermal MHT (WMD: 0.12, 95% CI: 0.04–0.21). The benefits of low dose MHT on TG was also concluded when comparing with conventional-dose estrogen (WMD: −0.18, 95% CI: −0.32 to −0.03). The results also showed that conventional MHT significantly decreased LDL-C (WMD: −0.35, 95% CI: −0.50 to −0.19), but increase TG (WMD: 0.42, 95%CI: 0.18–0.65) compared with tibolone. When comparing with the different MHT regimens, estrogen (E) + progesterone (P) regimen significantly increased TC (WMD: 0.15, 95% CI: 0.09 to 0.20), LDL-C (WMD: 0.12, 95% CI: 0.07–0.17) and Lp(a) (WMD: 44.58, 95% CI:28.09–61.06) compared with estrogen alone. Conclusion and Relevance: MHT plays a positive role in lipid profile in postmenopausal women, meanwhile for women with hypertriglyceridemia, low doses or transdermal MHT or tibolone would be a safer choice. Moreover, E + P regimen might blunt the benefit of estrogen on the lipid profile. Clinical Trial Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42018092924], identifier [No. CRD42018092924].